GeoLab, a measurement system for the geotechnical characterization of polluted submarine sediments. (October 2018) - Adamo, Francesco; Andria, Gregorio; Bottiglieri, Osvaldo; Cotecchia, Federica; Di Nisio, Attilio; Miccoli, Daniela; Sollecito, Francesca; Spadavecchia, Maurizio; Todaro, Francesco; Trotta, Amerigo; Vitone, Claudia
Highlights: A system for geotechnical measurement on submarine sediments is described. GeoLab increases speed, accuracy, and productivity in geotechnical lab tests. It allows to develop and test new procedures or innovative algorithms. A low noise/high stability power supply for transducers' excitation was designed. An highly reliable management software was proposed. Abstract: In this paper an integrated system (hardware and software), named GeoLab, for geotechnical measurement on submarine contaminated sediments is described; GeoLab permits to reduce the probability of human mistakes often made during long and repetitive manual operations and, to increase speed, accuracy, and productivity in geotechnical laboratory tests. A new, suitable management software was developed to permit the communication with different data acquisition platforms and to easily adapt software in case of changes in the laboratory procedures.